Single-shot method for measuring femtosecond bunch length in linac-based free-electron lasers - Z. Huang; K. Bane; Y. Ding; P. Emma (Physical Review Special Topics. Accelerators and Beams, 2010)
There is growing interest in the generation and characterization of femtosecond and subfemtosecond pulses from linac-based free-electron lasers (FELs). In this report, following the method of Ricci and Smith [Phys. Rev. ST Accel. Beams 3, 032801 (2000)PRABFM1098-440210.1103/PhysRevSTAB.3.032801], we investigate the measurement of the longitudinal bunch profile of an ultrashort electron bunch produced by these FELs. We show that this method can be applied in a straightforward manner at x-ray FEL facilities such as the Linac Coherent Light Source by slightly adjusting the second bunch compressor followed by running the bunch on an rf zero-crossing phase of the final linac. We find that the linac wakefield strongly perturbs the measurement, and through analysis show that it can be compensated in a simple way. We demonstrate the effectiveness of this method and wakefield compensation through numerical simulations, including effects of coherent synchrotron radiation and longitudinal space charge. When used in conjunction with a high-resolution electron spectrometer, this method potentially reveals the temporal profile of the electron beam down to the femtosecond and subfemotsecond scale.